1952
DOI: 10.1111/j.1939-0025.1952.tb01982.x
|View full text |Cite
|
Sign up to set email alerts
|

The picture-frustration technique as a measure of hostility and guilt reactions in adolescent psychopaths.

Abstract: F THE welter of contradictory theory concerning the aggressively 0 antisocial psychopath, certain assumptions regarding his hostility and guilt are readily accepted by most, if not all, authorities on this subject. It is the purpose of this study to test several of these basic assumptions under controlled experimental conditions. HYPOTHESESThe following hypotheses, derived from assumptions currently accepted either in part or in toto in clinical practice, are to be tested: 1) Psychopaths are more extrapunitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

1960
1960
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…This result is not an isolated one. Similar findings for such populations have been reported by Fry (1949), Holzberg andHahn (1952), andNorman andKleinfeld (1958). Kaswan, Wasman, and Freedman (1960) in a quite carefully designed and comprehensive investigation got somewhat more favorable results.…”
Section: West Virginia Universitysupporting
confidence: 89%
“…This result is not an isolated one. Similar findings for such populations have been reported by Fry (1949), Holzberg andHahn (1952), andNorman andKleinfeld (1958). Kaswan, Wasman, and Freedman (1960) in a quite carefully designed and comprehensive investigation got somewhat more favorable results.…”
Section: West Virginia Universitysupporting
confidence: 89%
“…This result is not an isolated one. Similar findings for such populations have been reported by Fry (1949), Holzberg and Hahn (1952), and Norman and Kleinfeld (1958). Kaswan, Wasman, and Freedman (1960) in a quite carefully designed and comprehensive investigation got somewhat more favorable results.…”
supporting
confidence: 89%
“…A measure of the intensity of aggressive reaction to frustration was designed in the belief that mild verbal aggression, such as "I don't agree," might characterize a different reactive process to frustration than that reflected by responses containing references to violent, uncontrolled aggression, such as "I'll break your neck." The failure of the present P-F scoring system to take into account such variations in intensity has been pointed out by Holzberg and Hahn (1952). This additional measure is expected to broaden the range of relationships between the P-F and other measures of aggression.…”
mentioning
confidence: 87%
“…Most validating studies have attempted to correlate a specific criterion of aggression with the P-F scoring term "extrapunitiveness" (E)-defined as the percentage of responses in which the individual turns his aggression outward, against the environment. For example, Fry (1949), Holzberg and Hahn (1952), Vane (1954), and Weinberg (1952 have all found that juvenile delinquents or adult criminal offenders fail to manifest more E on the P-F than nonantisocial subjects (5s), and have therefore concluded that the P-F is not valid. That such studies may represent too narrow an approach to validation is indicated by the APA Committee on Test Standards (1954, pp.…”
mentioning
confidence: 99%